Low platelet counts in pregnancy: an alarm signal for abruption! - Mundkur, Anjali; Nambiar, K. P. Murali Krishnan; Rai, Lavanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thrombocytopenia, defined as a platelet count less than 150 million/mm3, affects 6% to 10% of all pregnant women and other than anemia is the most common hematologic disorder in pregnancy. Methods: We studied all patients with thrombocytopenia in pregnancy from June 2012 to May 2013. There were 86 patients recruited into the study. Pregnant women with preeclampsia and suspected connective tissue disorder were also screened for thrombocytopenia. All women with platelet count of <1.50,000/µl during the study period were included. Results: Patients were grouped in to mild thrombocytopenia (platelet 100,000-149,999/µl), moderate thrombocytopenia (platelet 50,000-99,999/µl) and severe thrombocytopenia (platelet <49,999/µl. Pregnancy specific cause of thrombocytopenia was in 63 (73.2%) women and non-pregnancy specific were in 23(26.7%) patients. Conclusions: Preeclampsia and HELLP syndrome is more common cause of thrombocytopenia in pregnancy. Abruption can occur in patients with severe thrombocytopenia. Though platelet count is not routinely done in pregnancy it is advisable to do so as it may help in detecting gestational thrombocytopenia or other immune related condition.